A carbon-fabric/polycarbonate sandwiched film with high tensile and EMI shielding comprehensive properties: An experimental study. (1st November 2018) - Tang, Weijin; Lu, Longsheng; Xing, Di; Fang, Hezhengzi; Liu, Qiang; Teh, Kwok Siong
Abstract: Tremendous advancement in communications technologies and proliferation of personal electronics in recent decades give rise to electromagnetic pollution, which compels the development of electromagnetic interference (EMI) shielding materials. To this end, a nonwoven carbon fiber/polypropylene/polyethylene fabric (CEF-NF) with remarkable specific EMI shielding effectiveness (EMI-SE) was demonstrated previously which met commercial EMI requirements. The relatively low tensile strength of CEF-NFs (below 30 MPa) is, however, a problem that prevents their adoption in industrial applications. To address this problem, an ultra-thin (0.29 ± 0.01 mm) carbon-fabric/polycarbonate sandwiched film (simplified as CF/PC film) was prepared using a laminating process, in which a CEF-NF was used as a sandwich layer, securely contained between two PC films. The effects of laminating parameters—temperature and pressure—and structural parameters on the properties of the CF/PC film were investigated. Results illustrated that the infiltrating process of molten PC into the CEF-NF is enhanced with increasing laminating temperature and pressure, whereas the network structure of the fabric may be damaged under excessively high laminating parameters, which leads to the deterioration of its EMI shielding performance. With increasing carbon fiber (CF) concentration, the tensile strength and EMI-SE of this CF/PC film increase, and a ductile-brittle fracture transition appears. Under an optimal set of process parameters—195 °C laminating temperature, 6 MPa laminating pressure, 6 mm CF length, and 90% of CF concentration, this CF/PC film exhibits a tensile strength of 115.1 MPa—which is close to 5 × that of an identical CEF-NF—and 38.6 dB EMI-SE. Lastly, the ES/D/T (EMI-SE·Strength/Density/Thickness) index of this CF/PC film reaches 138320 dB MPa cm 2 ·g −1, which is higher than most competing materials reported in the literature.